(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
is study aims to analyze the changes in the function and policies of Hakka Weiwu from their inception to 2023. The research employed a combination of literature review, field surveys, and interviews with key stakeholders related to Hakka Weiwu to achieve this objective. The final research findings are based on interviews with 19 individuals closely associated with Hakka Weiwu, including Hakka Weiwu scholars, policymakers, Weiwu designers, and residents. Their insights and experiences provide a comprehensive overview of the development of Hakka Weiwu. The ultimate research results are as follows: From the establishment of Hakka Weiwu to the year 2023, both their functions and policies have undergone positive changes. These changes have transformed Hakka Weiwu from their traditional functional forms into modern, diversified structures encompassing roles in tourism, museums, education, and more. These transformations reflect the diversity and vitality of Weiwu in contemporary society. Meanwhile, government initiatives that began in the early 1990s have played a crucial role in formulating policies for the protection of Hakka Weiwu. These policies have been instrumental in supporting and promoting the preservation, development, and innovation of Hakka culture.